Relationships between nanostructure and dynamic-mechanical properties of epoxy network containing PMMA-modified silsesquioxane (eXPRESS Polymer Letters)
A new class of organic-inorganic hybrid nanocomposites was obtained by blending PMMA-modified silsesquioxane hybrid materials with epoxy matrix followed by curing with methyl tetrahydrophthalic anhydride. The hybrid materials were obtained by sol-gel method through the hydrolysis and polycondensation of the silicon species of the hybrid precursor, 3-methacryloxypropyltrimethoxysilane (MPTS), simultaneously to the polymerization of the methacrylate (MMA) groups covalently bonded to the silicon atoms. The nanostructure of these materials was investigated by small angle X-ray scattering (SAXS) and correlated to their dynamic mechanical properties. The SAXS results revealed a hierarchical nanostructure consisting on two structural levels. The first level is related to the siloxane nanoparticles spatially correlated in the epoxy matrix, forming larger hybrid secondary aggregates. The dispersion of siloxane nanoparticles in epoxy matrix was favored by increasing the MMA content in the hybrid material. The presence of small amount of hybrid material affected significantly the dynamic mechanical properties of the epoxy networks.